FAMILY’S VIEW REGARDING THE DECISION TO BE A CORNEA DONOR: A PHENOMENOLOGICAL STUDY - Baswedan, Rizki Hafidzah; Padmawati, Retna Siwi; Widyandana, Doni (Majalah Oftalmologi Indonesia, 2023)
Introduction and Objective: Family has an important role in the corneal donor process. Corneal extraction can be done when a potential donor dies, so it requires family involvement and support. The purpose of this study is to explore the family's view on the decision to be a cornea donor so that we can obtain a deep understanding on this issue. Methods: Phenomenological studies were conducted in Yogyakarta, Indonesia on families of prospective cornea donors (n=6) and registered cornea donor candidates (n=6). Data were collected using in-depth interviews and study documents. Data were analyzed using the Colaizzi’s method. Results: Family participants' knowledge and understanding of the urgency and procedure of corneal donors is the main point that constructs their view of corneal donors. Most family participants consider being corneal donors a good thing to do. All participants expressed their willingness to carry out the will of prospective donors, but there was no guarantee they would do so. Fifty percent of participants’ families are also interested in becoming corneal donors in consideration of religious organizations, educational background, and experience participating in activities with the Eye Bank and the donors. Conclusion: Families have an important role in the corneal donor process because they will carry out the will of prospective donors and serve as liaisons for the Eye Bank. Family involvement in the promotion of the cornea donor program is needed.